Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Project Based Learning - Siahaan, Erpina; Gaol, Resdelia Lumban (EduCurio: Education Curiosity, 2024)
This study aims in general the purpose of this study is to improve student learning outcomes in writing procedure text. While specifically the objectives of this study are: (1) improving the implementation of procedure text learning through a project-based learning model, (2) increasing the supporting factors for the success of procedural text learning. (3) overcome the obstacles faced in the implementation of procedure text learning, (4) efforts that must be made by teachers in overcoming obstacles in learning procedure text. The research method used in this study is classroom action research with a project-based learning model. The population in this study is grade VIII students of SMP Eka Pendawa Sakti where as a sample of grade VIII Mandiri. To collect data in this study using test and non-test instruments, as a test instrument using 20 multiple-choice questions and for non-test instruments using assessment rubrics and observations. Based on the results of written and non-test tests this research can be concluded: 9 students are in the satisfactory category 29% of 31 students, 20 students in the good category 65%, 2 students in the sufficient category 6%.